Pharmacological activities of cinnamaldehyde and eugenol: antioxidant, cytotoxic and anti-leishmanial studies - Sharma, U. K.; Sharma, A. K.; Gupta, A.; Kumar, R.; Pandey, A.; Pandey, A. K. (Cellular and Molecular Biology, 2017)
The present study reports the antioxidant, cytotoxic and anti-leishmanial activities of cinnamaldehyde and eugenol. Both the compounds are naturally present in cinnamon and bay leaf. Eugenol is abundantly present in clove. The antioxidant potential was measured in terms of reducing power (FRAP assay), nitric oxide (NO) radical scavenging ability and anti-lipid peroxidative activities. MTT assay was used to evaluate the effect of test compounds on cell viability of prostate cancer cell line (PC-3) as well as for the assessment of in vitro growth inhibition of promastigotes as a measure of anti-leishmanial activity.  Eugenol exhibited considerable NO radical scavenging (63%) and reducing abilities (FRAP value 127í—104 µM/mM) while cinnamaldehyde showed comparatively better protective efficacy against lipid peroxidation in rat brain and kidney homogenates (up to 40%). Cinnamaldehyde also displayed substantial cytotoxic activity (75%) against PC-3 cell line. Both the compounds exhibited moderate anti-leishmanial activity and IC50 values for eugenol and cinnamaldehyde were found to be 0.681 g/ml and 1.426g/ml, respectively. The study revealed that both the test compounds have noticeable antioxidant and cytotoxic activities.